Conceptual model for assessing logistics maturity in smart city dimensions - Glauber Ruan Barbosa Pereira; Luciana Gondim de Almeida Guimar\~aes; Yan Cimon; Lais Karla da Silva Barreto; Cristine Hermann Nodari (Administrative Sciences, 2023)
The advancement of new technologies and the increasingly inseparable presence of logistics systems in the daily life of cities, industries, companies, and society has been modifying how logistics processes are implemented in these environments based on technological innovations, internet, virtual businesses, mobility, and the use of multi-channel distribution. Together with these changes, urban centers have been connecting to the smart city concept as the understanding of this theme advances into the debate and improvements in the agendas of either public or private management. This research proposes a conceptual model for evaluating logistics maturity in the smart city dimensions. The method has a qualitative, exploratory, and descriptive approach, supported by the Delphi method, which uses a questionnaire and interview as a data collection instrument with specialists on the subject. We identified that qualifying logistics in the urban environment is complex and requires a specialized look at identifying cities' structural, geographic, regional, social, and environmental characteristics. As a social-technological contribution, the proposition of the logistics maturity assessment scale in smart city dimensions can serve as an evaluative model of logistics, which means helping in urban planning and strategic management of cities, offering smarter solutions to the realities of urban spaces.
Keywords: 350; logistics; maturity; smart city; smart city dimensions